An Investigation of Interpersonal Metadiscourse Markers as Persuasive Strategies in Donald Trump’s 2016 Campaign Speeches - Parisa Etemadfar; Ehsan Namaziandost (Critical Literary Studies, 2020)
Interpersonal metadiscourse is considered as a significant mean of smoothing communication between the speaker/writer and listener/reader. The present study intends to explore the concept and type of interpersonal metadiscourse markers employed by Donald Trump’s campaign speeches as a persuasive strategy. Descriptive qualitative research design is used in the present study. Dafouz’s (2008) classification of interpersonal metadiscourse markers was employed to analyze the gathered data. The results revealed that Trump made use of all categories of interpersonal metadiscourse markers namely hedges, certainty markers, attributors, attitude markers, and commentaries, in his campaign speeches. The frequency of attitude markers and commentaries was more than other types of metadiscourse markers in Trump’s campaign speech, which demonstrates that he attempted to persuade the public to vote for him through making an emotional link.